2015
DOI: 10.1007/s00068-015-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

A small case series of aortic balloon occlusion in trauma: lessons learned from its use in ruptured abdominal aortic aneurysms and a brief review

Abstract: EVTM, including the usage of ABO, can be initiated on patient arrival and is feasible. Further data need to be collected to investigate proper indications for ABO, best clinical usage, results and potential complications. Accordingly, the ABOTrauma Registry has recently been set up. Existing experiences of EVTM and lessons from the endovascular treatment of rAAA may be useful in trauma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…These studies were predominantly older in publication date but were still eligible for inclusion. Therefore, after final quantitative synthesis, 89 articles were selected, including 28 case reports [11, 2046], 25 case series [10, 4771], and 36 (retrospective) cohort studies [12, 72–105]. Also 8 reviews were identified but not included in calculations, due to concern for double counting of unique cases [5, 13, 14, 106110].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were predominantly older in publication date but were still eligible for inclusion. Therefore, after final quantitative synthesis, 89 articles were selected, including 28 case reports [11, 2046], 25 case series [10, 4771], and 36 (retrospective) cohort studies [12, 72–105]. Also 8 reviews were identified but not included in calculations, due to concern for double counting of unique cases [5, 13, 14, 106110].…”
Section: Resultsmentioning
confidence: 99%
“…3), 56.1 mmHg in rAAA and 52.4 mmHg other types of patients in established hemorrhagic shock, among the 23 studies [10, 12, 22, 25, 2931, 34, 36, 40, 41, 44, 45, 47, 48, 52, 55, 58, 59, 62, 66, 71, 97, 104, 105, 111] reporting pre-REBOA and post-REBOA SBP values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,6,[8][9][10] It is one of the methods that may be used within EVTM, which gathers together different tools for bleeding control. 2,6 The indications and Figure 2. Frontal view of ABO in zone III applying partial occlusion with partially inflated balloon (red arrow) and a looped ABO catheter (white arrow).…”
Section: Discussionmentioning
confidence: 99%
“…The usage of ABO in severe trauma for hemodynamic stabilization is increasing, but so far there are no clear indications, guidelines or contraindications with regard to its usage in trauma management. [1][2][3][4][5] In contrast to emergency thoracotomy and aortic clamping, the occlusion level can be adjusted and established by fluoroscopy (unpublished data). Another advantage of ABO over external aortic clamping lies in the theoretical possibility of partial ABO (pABO), i.e.…”
Section: Introductionmentioning
confidence: 99%